Bronchoalveolar lavage profiles in uncontrolled wheezy children compared by asthma predictive index. Issue 1 (18th October 2021) - Ezmigna, Dima; Brown, Mark; Daines, Cori; Morgan, Wayne
Abstract: Objective: The asthma predictive index (API) predicts later asthma in preschoolers with frequent wheeze. We hypothesized that airway cytology differs between API positive (API+)/negative (API−) children with uncontrolled/recurrent wheezing with dominance of eosinophils in API+ and neutrophils in API− groups respectively. The main objective of this study is to compare bronchoalveolar lavage (BAL) cell profiles in API+/API− children with recurrent wheezing unresponsive to inhaled corticosteroids (ICS). Design: Retrospective analysis of BAL in 43 children, 3–36 months (median: 14 months) receiving ICS (31 API+, 12 API−). BAL cell differential counts, bacterial/viral cultures, and lipid‐laden macrophage percentages were analyzed. Cell counts presented as median (range). Results: Neutrophil percentages were increased in both groups (API− 16% [1%–76%]; API+ 42% [1%–95%]; p = NS). Cell percentages were similar for lymphocytes (API− 12% [1%–30%]; API+ 7% [1%–37%]), and macrophages (API− 67.5% [12%–97%]; API+ 41% [2%–94%]). Eosinophil percentages were low in both groups (API− 1% [1%–2%]; API+ 1% [1%–11%]). There was no difference in cellular distributions using absolute cell counts comparing API groups. Bacterial cultures were positive in 18 (60%) API+ and 5 (41%) API− patients ( p = 0.10). Conclusion: Cell profiles do not differ between API groups in children ≤36 months with recurrent wheezing unresponsive to ICS. Neutrophil percentages and total granulocyte count correlate with positive bacterial cultures independent of API status. Persistent bacterial bronchitis likely plays an important role in the persistence of symptoms unresponsive to ICS therapy regardless of API status with a trend to more positive cultures in API positive children.